What implementation strategies are relational? Using Relational Theory to explore the ERIC implementation strategies - Bartley, Leah; Metz, Allison; Fleming, W. Oscar (Frontiers in Health Services, 2022)
The identification and use of implementation strategies in implementation research and practice have strengthened our understanding of the implementation process as well as the causal pathways between mechanisms, strategies, and implementation outcomes. Although these contributions have advanced the application of strategies, there is still a need to learn more about how strategies might integrate relational exchanges and interactions. The inclusion of critical perspectives has been limited in implementation science, and theories such as Relational Theory can expand our understanding of the relational nature of implementation and enhance rigor through alternative theoretical applications. This study applied Relational Theory through a qualitative directed content analysis of the 73 Expert Recommendations for Implementation Change (ERIC) implementation strategies and examine relational components in strategy descriptions. Three reviewers used the structured approach to review and categorize the implementation strategies based on the Relational and Transactional Strategy Continuum measure, which operationalizes types of interactions, exchanges and alliances. Relational alliance strategies are those in which there is mutual growth and accountability, frequent interaction, shared power, and potential vulnerability. Operational alliances include forms of working exchanges between parties with balanced transactional and relational features. Operational alliances can be somewhat interactive in nature, with minor exchanges and limited accountability. Transactional alliance strategies are mostly uni-directional, influenced by power differentials, and do not require mutual growth, commitment, or exchange; thus, the power of growth is inherently one-sided. Results from the review suggest more implementation strategies with relational alliance features (highly relational, n = 17, semi-relational, n = 19) compared to transactional (highly transactional, n = 9, semi-transactional, n = 10) and 18 strategies coded as operational alliances. The qualitative review revealed opportunities to further expand how relational exchanges are considered within the implementation strategies descriptions, as well as the role of actors and power dynamics within strategy exchanges. The Relational and Transactional Strategy Continuum measure can help practitioners and researchers consider the sequencing, pairing, and impact on outcomes of different types and combinations of strategies in implementation practice and research. Additionally, the measure can support reflection on strategies that promote positive alliances, frequent connections, bi-directional communication, and power sharing.